Antiochia in der Spätantike: Prolegomena zu einer archäologischen Stadtgeschichte - Brands, Gunnar (Hans-Lietzmann-Vorlesungen, 2016)
"Our image of Antioch on the Orontes, a metropolis of the Roman world, is largely shaped by the reports of ancient authors. By comparison, the archeological image of the city of late antiquity has remained essentially invisible. It has become apparent over time that the city underwent radical reconstruction beginning from the 4th century as the result of pillage and natural disasters as well as demographic and economic change"--Provided by publisher